Out of sight, out of mind: the invisibility of female African athletes in sports and exercise medicine research - Mkumbuzi, Nonhlanhla Sharon; Chibhabha, Fidelis; Zondi, Phathokuhle Cele (BMJ Publishing Group, 2022)
In recent years, there has been a notable increase in the participation of females in sport, as well as professionalism of female sport.1 Sports and exercise medicine (SEM) literature has, however, failed to mirror this progress, as female athletes continue to be on the margins of methodological, theoretical and empirical research.2 The absence of the female narrative in the scientific literature is even more pervasive for female athletes in Africa, which presents various challenges for athletes and clinicians. This editorial highlights the challenges associated with the scarcity of research on female African athletes. Much of the current scientific evidence on athletes fails to account for the intersection of gender, race, culture and economics3—factors which compound the difficulties faced by female athletes. In particular, the journey of the female African athlete is significantly influenced by the following: societal expectations, culturally driven perceptions, and (lack of) access to opportunities, sports infrastructure and financial support.4 As such, interventions that do not consider the intersection between biology and the …